Pretreatment of kenaf (Hibiscus cannabinus L.) biomass feedstock for polyhydroxybutyrate (PHB) production and characterization. (June 2019) - Saratale, Rijuta Ganesh; Saratale, Ganesh Dattatraya; Cho, Si Kyung; Kim, Dong Su; Ghodake, Gajanan S.; Kadam, Avinash; Kumar, Gopalakrishanan; Bharagava, Ram Naresh; Banu, Rajesh; Shin, Han Seung
Graphical abstract: Highlights: First attempt to utilize kenaf biomass (KB) for cost effective, sustainable PHB production. Studied various pretreatment methods to utilize KB as feedstock for PHB production. Pretreatment process enhanced saccharification of KB without fermentation inhibitors. PHB produced exhibited similar structural and thermal properties alike standard PHB. PHA accumulation, PHB yield using KB hydrolsates was similar to the synthetic sugars mixture. Abstract: Kenaf biomass (KB) was employed as feedstock for the synthesis of polyhydroxybutyrate (PHB) using Ralstonia eutropha to replace conventional petroleum-derived polymers. Various pretreatments followed by enzymatic saccharification were applied to release monomeric sugars from KB for PHB production. The effects of increasing concentration of Na2 CO3  + Na2 SO3 (NaC + NaS) pretreated KB hydrolysates (20–40 g/L) on PHB production were investigated. NaC + NaS pretreated KB hydrolysates (30 g/L) exhibited maximum 70.0% PHA accumulation, with PHB titers of 10.10 g/L and PHB yields of about 0.488 g/g of reducing sugar produced within 36 h of fermentation. PHA accumulation, PHB yield and R. eutropha growth performance using KB hydrolysates were found to be comparable with those of synthetic sugar mixture. Characterization of the produced PHB in terms of crystalline structure, and thermal properties was done using various analytical techniques and results coincide with standard PHB. Thus, green liquor pretreated KB hydrolysates deliver a promising and economically feasible carbon substrate for PHB production.